Characterization and the impact of in vitro simulated digestion on the stability and bioaccessibility of carotenoids and their esters in two Pouteria lucuma varieties. (30th June 2020) - Gómez-Maqueo, Andrea; Bandino, Elisa; Hormaza, José I.; Cano, M. Pilar
Highlights: Lucuma fruits are rich sources of carotenoids (4–6 mg/100 g fresh weight). Pulps had a high qualitative diversity of 9 xanthophylls, 9 carotenes and 15 xanthophyll esters. Violaxanthin and antheraxanthin esters were the main carotenoids in lucuma fruits. Carotenoids were deposited in amylochromoplasts and globular chromoplasts. Carotenoids presented high stability but low bioacessibility. Abstract: Lucuma is a starchy orange-yellow fruit native to the Andean region. It is widely consumed in Latin America and has been recently adapted to the agronomical characteristics of the south region of Spain. However, its carotenoid profile has never been reported. The aim of this study was to characterize the carotenoid and carotenoid ester composition of lucuma pulps (var. Molina and Beltran) and assess their bioaccessibility with an in vitro simulated gastrointestinal digestion according to the INFOGEST® methodology. The carotenoid profile in lucuma pulps revealed a high qualitative diversity composed of 33 compounds, corresponding to 9 free xanthophylls, 9 hydrocarbon carotenes and 15 xanthophyll esters. (13 Z )-violaxanthin, (all- E )-violaxanthin and (all- E )-antheraxanthin were the most abundant carotenoids in lucuma fruits and were naturally present as xanthophyll esters: (all- E )-antheraxanthin 3-O-palmitate, (all- E )-violaxanthin laurate and (all- E )-violaxanthin palmitate. Carotenoids were stable during in vitro digestion; however, their release from the food matrix was limited which contributed to their low bioaccessibility.